Within-Season Trends in Abundance and Distribution of Humpback Whales (Megaptera novaeangliae) in the Antarctic Peninsula Region - Johannessen, John Elling Deehr (UiT Norges arktiske universitet, 2020)
Klarer ikke gjennomføre sak: Failed to perform step 1 in Navigate Stage 'Activate Adobe Reader + Click Center' on page 'Read PDF' - Could not identify process owning the current foreground window Fine-scale knowledge of cetacean abundance and distribution throughout the Antarctic Peninsula (AP) is lacking yet essential for effective ecosystem-based fisheries management (EBFM). We investigated an important area both for migratory humpback whales (Megaptera novaeangliae) and Antarctic krill (Euphausia superba) fisheries to assess potential spatio-temporal interactions, for use in adaptive EBFM and marine protected area (MPA) consideration. We collected data using tourist cruise ships as platforms of opportunity during the austral summer of 2019/2020, followed by analysis using spatial hurdle surface modeling and satellite derived oceanographic covariates. Our results indicate that small numbers of humpback whales are present in the Bransfield and Gerlache Straits at the start of the austral summer (November), becoming increasingly abundant in late December in the northern Gerlache Strait, but becoming more dispersed throughout the northern AP in late January. Using relative abundances, we estimate that whales consume approximately 0.5 – 3.3 million tons of Antarctic krill during their feeding season. Based on our results and catch data in the study area, we conclude that there is minimal spatio-temporal overlap between humpback whales and fishery activity our study period of November – January. However, there is potential for significant interaction between the two later in the feeding season, with fisheries potentially harvesting 5.9 – 11.6% of monthly humpback whale Antarctic krill consumption in highly overlapping regions in April. Research effort needs to extend later in the season to properly quantify the spatio-temporal overlap.